Teaching-Material of Elementary Social Studies; Constructing a Powerful Approach to Local Wisdom in Indonesia - Aris Suherman; Widodo Winarso (International Journal of Education and Humanities, 2021)
Learning is a process of active behavior, interactive and constructive. The learning process is used as a social context that needs attention. Social studies learning must be able to become and strengthen the values of local wisdom as a symbol of the character's identity of students. Then there needs to be an analysis of the development pattern of social science learning material materials based on local wisdom to shape student character. This study aims to describe the development of social science teaching materials based on local wisdom. The resulting teaching material products are developed by following Borg & Gall's. Product feasibility is measured through product validity, product practicality, and product effectiveness. The data collection techniques of this research were interviews, questionnaires, observations, tests, and documentation. The research results show that the development of social science learning materials based on local wisdom can help teachers in their efforts to understand students and connect learning material with the potential of the region. The development of social studies learning material based on local wisdom can help students understand their area's potential. This is based on the average pre-test score of 33,70 to 55,80. The average post-test score increased by an average score of 0.35, in the moderate category